Broadband for a sustainable digital future of rural communities: A reflexive interactive assessment. (August 2017) - Pant, Laxmi Prasad; Hambly Odame, Helen
Abstract: Stakeholders face an ongoing challenge of assessing impacts of large-scale interventions, such as rural broadband infrastructure, which involve both social and technological change. In order to determine immediate benefits, intermediate outcomes and long-term societal impacts of broadband Internet, this paper integrates latest approaches to assess social and technological change, which are known respectively as 'reflexive learning' and 'reflexive governance'. This paper contextualises the integrated framework using case studies of broadband access and use among small businesses and community organisations from the first release areas of the heavily invested high-speed broadband network known as EORN (Eastern Ontario Regional Network) in Canada. EORN represents a major public-private partnership for rural telecommunications which began in 2009 and ended its first phase in 2014. Findings revealed location and sector specific benefits of broadband that rural small businesses and community organisations have realised from increased access to (including availability and affordability) as well as reliability of Internet connections. Also evident were early signs of transitions to more resilient and sustainable rural communities. Partly because of a new initiative, research evidence, however, was not sufficiently robust to determine system-level impacts or structural changes, such as closing rural-urban price gaps and reducing the price of rural broadband services. Highlights: Broadband technology assessment involves aspects of social as well as technical change. Develops a hybrid methodology integrating program assessment and technology assessment. Uses this methodology to assess a major Canadian rural broadband investment program. Broadband Internet is an essential service for regional and rural innovation. Broadband Internet potentially facilitates transitions to rural resilience and sustainability.